Clinical and Prognostic Significances of Cytokeratin 19 and KIT Expression in Surgically Resectable Pancreatic Neuroendocrine Tumors - Eun-Mi Son; Joo Young Kim; Soyeon An; Ki-Byung Song; Song Cheol Kim; Eunsil Yu; Seung-Mo Hong (Korean Society of Pathologists & the Korean Society for Cytopathology, 2015)
Background: Pancreatic neuroendocrine tumors (PanNETs) are malignant endocrine neoplasms that present diverse clinical behaviors. Therefore, identification of biomarkers of PanNETs is important for stratification of the prognosis of PanNET patients. Recently, cytokeratin 19 (CK19) and KIT expression were reported to have prognostic significance in PanNET patients. Methods: To identify their prognostic significance, CK19 and KIT protein expression were assessed in 182 surgically resected PanNETs and compared with clinicopathologic factors. Results: Of 182 PanNETs cases, CK19 and KIT expression was noted in 97 (53.3%) and 16 (8.8%) cases, respectively. PanNET patients with CK19 expression had larger tumors (p=.006), higher World Health Organization (WHO) grade (p=.002) and pT classification (p<.001), increased distant metastasis (p=.004), and lymphovascular (p=.012) and perineural (p=.019) invasion. Similarly, those with KIT expression had larger tumors (p=.030), higher WHO grade (p=.001), advanced pT classification (p<.001), distant metastasis (p=.001), and lymphovascular invasion (p=.014). The 5-year survival rate for PanNET patients with KIT expression was significantly lower (62%) than that of patients without KIT expression (77%, p=.011), as determined by univariate but not by multivariate analyses. Conclusions: CK19 and KIT expression correlate with higher metastatic potential and advanced disease stage, and KIT expression is associated with worse survival in PanNET patients.